Relationship between physical activity and hyperglycemia in kyai and teachers in Islamic boarding school in Yogyakarta - Afrida Nur Hidayati; Hamam Hadi; Dewi Astiti (Alma Ata University Press, 2017)
ABSTRACTBackground: Riskesdas 2013 stated that 15 provinces had a prevalences of Diabetes Melitus disease above national prevalence. DIY province is one province with high prevalence of DM disease as many as 3,0%. Hyperglicemia is a sign of DM disease. Physical activity is one of the management programs in hyperglycemia patients. Physical activity plays a role in controlling the body’s blood glucose by turning glucose into energy.Objectives: To know the correlation between physical activity and hyperglikemia on Kyai and teacher in Islamic Boarding School in Special Region Yogyakarta (DIY).Methods: The study was an observational analytic study with Cross Sectional design. Population in this research was Kyai and teacher at Islamic Boarding School of DIY which amount 579 people. The minimum number of samples obtained was 184 respondents with probability proportional to size (PPS) sampling technique. Bllod Glucose data using Easy Touch and physical activity data using International Physical Activity Questionaire (IPAQ) questionnaire. Data analysis in the form of frequency distribution, mean different test (T-test) and Chi Square test is done by using SPSS software.Results: Based on T-test showed that there was a difference of blood glucose between group of physical activity less with group activity enought but the difference was not significant with t-value = 0,446, p-value = 0,656, and mean different = 3,127, and result of Chi Square test showed no significant correlation between physical activity and hyperglycemia with p-value = 0,969.Conclusions: There was no correlation between physical activity and hiperglikemia.KEYWORDS: hyperglicemia, Islamic Boarding School, Kyai, physical activity teacher